Prognostic and Predictive Impact of Primary Tumor Sidedness for Previously Untreated Advanced Colorectal Cancer. (1st June 2021) - Yin, Jun; Cohen, Romain; Jin, Zhaohui; Liu, Heshan; Pederson, Levi; Adams, Richard; Grothey, Axel; Maughan, Timothy S; Venook, Alan; Van Cutsem, Eric; Punt, Cornelis; Koopman, Miriam; et al.
Abstract: Background: Unplanned subgroup analyses from several studies have suggested primary tumor sidedness (PTS) as a potential prognostic and predictive parameter in metastatic colorectal cancer (mCRC). We aimed to investigate the impact of PTS on outcomes of mCRC patients. Methods: PTS data of 9277 mCRC patients from 12 first-line randomized trials in the ARCAD database were pooled. Overall survival (OS) and progression-free survival (PFS) were assessed using Kaplan-Meier and Cox models adjusting for age, sex, performance status, prior radiation/chemotherapy, and stratified by treatment arm. Predictive value was tested by interaction term between PTS and treatment (cetuximab plus chemotherapy vs chemotherapy alone). All statistical tests were 2-sided. Results: Compared with right-sided metastatic colorectal cancer patients (n = 2421, 26.1%), left-sided metastatic colorectal cancer patients (n = 6856, 73.9%) had better OS (median = 21.6 vs 15.9 months; adjusted hazard ratio [HRadj ] = 0.71, 95% confidence interval [CI] = 0.67 to 0.76; P < .001) and PFS (median = 8.6 vs 7.5 months; HRadj = 0.80, 95% CI = 0.75 to 0.84; P < .001). Interaction between PTS and KRAS mutation was statistically significant ( P interaction < .001); left-sidedness was associated with better prognosis among KRAS wild-type (WT) (OS HRadj = 0.59, 95% CI = 0.53 to 0.66; PFS HRadj =0.68, 95% CI = 0.61 to 0.75) but not among KRAS mutated tumors. Among KRAS -WT tumors, survival benefit from anti-EGFR was confirmed for left-sidedness (OS HRadj = 0.85, 95% CI = 0.75 to 0.97; P  = .01; PFS HRadj = 0.77, 95% CI = 0.67 to 0.88; P < .001) but not for right-sidedness. Conclusions: The prognostic value of PTS is restricted to the KRAS -WT population. PTS is predictive of anti-EGFR efficacy, with a statistically significant improvement of survival for left-sidedness mCRC patients. These results suggest treatment choice in mCRC should be based on both PTS and KRAS status.